USING TEAM-PAIR-SOLO (TPS) TO IMPROVE READING COMPREHENSION - I Kadek Marajana; Ni Luh Putu Dian Sawitri; Ni Wayan Krismayani (Academic Journal on English Studies (AJOES), 2022)
This study was aimed at finding out whether using TPS could improve the subjects’ reading comprehension. The subjects were the eleventh-grade students of SMA Pariwisata Saraswati Klungkung in academic year 2021/2022, especially the students of XI MIPA 1 class which consisted of 33 students. Based on the result of pre-test, it was found that many students had problems in identifying general information, specific information, textual meaning and textual reference. Therefore, the TPS technique was carried out and divided into two cycles. The data were obtained by administering post-test 1 and post-test 2 at the end of each cycle. The mean scores of pre-test, posttest 1, and post-test 2 were respectively 58.30, 67.57, and 74.21. The result of the post-tests showed that there were significant improvements toward subjects reading comprehension. Moreover, the result of the questionnaire showed that the subjects gave positive responses toward the use of TPS technique. In conclusion, this study proved that reading comprehension of the eleventh-grade students of SMA Pariwisata Saraswati Klungkung in the academic year 2021/2022 could be improved through the TPS technique.